The Effect of Approach Group Counseling REBT on Anxiety Reduction Student Communication - Kevin Gusti Kesuma; I Indiati; S Sugiyadi (Prosiding University Research Colloquium, 2022)
This study aims to determine the effect of group counseling with the Rational Emotive Behavior Therapy approach on reducing communication anxiety in students at SMP N 1 Kranggan Temanggung. This study uses the One Group Pretest Posttest Design. The samples taken in this study were 8 students as the experimental group. The sampling approach used a purposive sampling approach because in accordance with the characteristics of the study, in this study students had high communication anxiety. The data analysis method used is Parametric analysis Paired sample t-test with the help of SPSS 24.0 The results showed that the REBT approach group counseling had an effect on students' communication anxiety. This is evidenced by the results of the Parametric Statistics Paired sample t-test with a significance value probability (2-tailed) of 0.001 < 0.05. There is a difference in the average communication anxiety questionnaire score of 23% from the results of the communication anxiety questionnaire pretest and the communication anxiety posttest results. The results of this study can be concluded that the REBT approach group counseling has an effect on reducing students' communication anxiety.